DOI: 10.11606/t.59.2013.tde-26032013-100917
|View full text |Cite
|
Sign up to set email alerts
|

Influência do padrão de beleza veiculado pela mídia na satisfação corporal e escolha alimentar de adultos

Abstract: Agradeço aos meus pais, Eduardo e Ana, meus amigos, confidentes e conselheiros, por todo suporte para que eu pudesse me dedicar e mergulhar neste trabalho de corpo e alma.Ao Prof. Sebastião, por sua orientação e seus sábios conselhos profissionais e pessoais durante esses anos de trabalho e convivência. Sua paciência, dedicação e sabedoria foram fundamentais para que eu me tornasse uma "quase pesquisadora independente"!!!! À Prof a . Telma que, além de professora e orientadora, também tornou-se uma grande amig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
16

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 107 publications
(181 reference statements)
0
9
0
16
Order By: Relevance
“…Currently, advertising is another important influence on eating behavior. Several studies have shown a positive association between the hours spent watching television and the weight of individuals (Laus, 2012). Contento (2010), Nestle et al (1998), Pollard et al (2002) state that the media is capable of shaping numerous aspects related to food, and, according to Laus et al (2011), this influence occurs through food consumption patterns and the established ideals of beauty.…”
Section: Media and Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, advertising is another important influence on eating behavior. Several studies have shown a positive association between the hours spent watching television and the weight of individuals (Laus, 2012). Contento (2010), Nestle et al (1998), Pollard et al (2002) state that the media is capable of shaping numerous aspects related to food, and, according to Laus et al (2011), this influence occurs through food consumption patterns and the established ideals of beauty.…”
Section: Media and Behaviormentioning
confidence: 99%
“…Based on this, some researchers have been studying the effect of media images on eating behavior and have already found evidence that these cultural norms have a significant impact on their diet. Experimental studies of the association between these variables have used questionnaires as an evaluation measure of the amount of food ingested after visualizing stimuli or attitudes suggestive of eating disorders (Laus, 2012).…”
Section: Media and Behaviormentioning
confidence: 99%
“…Researches in the last two decades have demonstrated that body dissatisfaction was not confined to people diagnosed with eating disorders or some specific body image disorder, but affects the majority of people and is more prevalent within women (Laus, 2013).…”
Section: Body Image: a Brief Overview Focusing On Women's Bodymentioning
confidence: 99%
“…Os ideais de beleza responsáveis pela insatisfação corporal são transmitidos em sua maioria pela mídia, sendo que a não correspondência a este ideal pode ser determinante na alteração da percepção da imagem corporal do indivíduo. Efeito este, que pode ser observado até em crianças, uma vez que os mesmos estão expostos a um culto pelo corpo ideal preconizado pela sociedade e influenciado fortemente pela mídia (LAUS, 2012).…”
Section: Introductionunclassified